2012
DOI: 10.17231/comsoc.23(2012).1353
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of cancer news coverage trends: a comparison of three comprehensive content analyses

Abstract: Abstract:Cancer stories (N = 5,327) in the top 50 U.S. newspapers were analyzed by a team of four coders and the results were compared with the earliest analyses of this type (from 1977 and 1980). Using cancer incidence rates as a comparison, three cancers were found to be consistently underreported (male Hodgkin's, and thyroid) and four cancers were found to be consistently overreported (breast, blood/Leukemia, pancreatic, and bone/ muscle). In addition, cancer news coverage consistently has focused on treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
(12 reference statements)
4
11
2
Order By: Relevance
“…Similarly to other content analyses analyzing newspaper reporting of other health issues [36][37][38][39], we found that air pollution stories contained more threat information than efficacy information. It is important that newspapers report about the threat of air pollution on health, as this informs the public on the need for action.…”
Section: Discussionsupporting
confidence: 75%
“…Similarly to other content analyses analyzing newspaper reporting of other health issues [36][37][38][39], we found that air pollution stories contained more threat information than efficacy information. It is important that newspapers report about the threat of air pollution on health, as this informs the public on the need for action.…”
Section: Discussionsupporting
confidence: 75%
“…In this regard, it is noteworthy that others have identified the absence of incident and mortality data in news coverage of cancer. A content analysis of 2003 US newspapers finding only one in 20 stories reported mortality data [28]. Similarly, an Australian resource for friends of young people with cancer, where one might expect to find such information made explicit, says only that: "Most cancers can be treated and survival rates are increasing all the time" [29].…”
Section: An Inevitable Decline Towards Deathmentioning
confidence: 99%
“…The 2014 Hollywood movie about youth cancer, The Fault in Our Stars [30], caused some concern among clinicians because of its 'unrealistic' portrayal of the low likelihood of survival [31]. The overrepresentation of death as the outcome of cancer in young people by the entertainment industry, and the relative absence of mortality rates in news reports, underscores the importance of "cultivating accurate illness representations" [28]. This is not a simple matter, however, as the public representation of cancer, particularly in young people, is heavily inscribed with social and political meaning.…”
Section: An Inevitable Decline Towards Deathmentioning
confidence: 99%
“…However, mass media news articles may cover the topic of cancer in a variety of different ways (Bell & Seale, ). News articles commonly cover the topic of cancer by discussing factual information and stories about nonfamous individuals with cancer (Jensen, Moriarty, Hurley, & Stryker, ). In this research, we experimentally assessed the effects of factual news articles and news articles that contain an emotive narrative about a nonfamous person on cervical screening intention, and the process through which such effects occur.…”
Section: Introductionmentioning
confidence: 99%